2019
DOI: 10.1177/1545968319829455
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Structural Changes in Triceps Surae After a 1-Year Daily Self-stretch Program: A Prospective Randomized Controlled Trial in Chronic Hemiparesis

Abstract: Supplementary material for this article is available on the Neurorehabilitation & Neural Repair website along with the online version of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…It may be interesting, for physiotherapists, to determine, when possible and in real time, IMA variations consequent to the shifting of patients’ postures (from supine to a seated position), different seated postures (with aids and supports), or from a sitting to a standing position. In addition, the amount of IMA can be used as an outcome in the assessment of the effectiveness of physiotherapy treatments aimed to maintain muscle length and extensibility, such as stretching protocols and manual therapy treatments [ 14 , 16 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be interesting, for physiotherapists, to determine, when possible and in real time, IMA variations consequent to the shifting of patients’ postures (from supine to a seated position), different seated postures (with aids and supports), or from a sitting to a standing position. In addition, the amount of IMA can be used as an outcome in the assessment of the effectiveness of physiotherapy treatments aimed to maintain muscle length and extensibility, such as stretching protocols and manual therapy treatments [ 14 , 16 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When combined with the acupoint injection of O3, this therapy has even more beneficial effects [70]. Pradines et al [71] reported that guided self-rehabilitation, combined with conventional rehabilitation, increased muscle fascicle length, extensibility, and ambulation speed more than conventional rehabilitation alone in patients with chronic hemiparesis. Atan et al [72] reported that body weight-supported treadmill training improved walking distance and balance ability, relieved fatigue, and also reduced pain in patients with moderate to advanced PD.…”
Section: Other Relevant Findingsmentioning
confidence: 99%
“…In addition, the volume, moment, and activation of the plantar flexor muscle of stroke survivors were all lower than that of healthy adults, and fascicle lengths and extensibility were decreased due to stiffness [3,9]. A previous study showed that stretching the lower limb muscles, including the plantar flexor muscle, improved ambulation speed and the structural changes in the muscle [9]. However, there are only a few studies that examine how this altered muscle structure affects physical function.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, chronic stroke survivors with a gait speed slower than 0.8 m/s showed thinner quadriceps muscle thickness and the worst static balance compared to healthy adults [8]. In addition, the volume, moment, and activation of the plantar flexor muscle of stroke survivors were all lower than that of healthy adults, and fascicle lengths and extensibility were decreased due to stiffness [3,9]. A previous study showed that stretching the lower limb muscles, including the plantar flexor muscle, improved ambulation speed and the structural changes in the muscle [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation